Research methods for public administrators - Johnson, Gail, 1947- (Quorum Books, 2002)
A simple, straightforward presentation of the concepts, methods, and tools of research in the public sector, emphasizing the "how" of research - how to do it, how to make sense of it--all in one reader-friendly volume stripped of arcane theory and impenetrable mathematics. Without jargon or mathematical theory to hinder a quick understanding and use, here are the research tools and techniques you can grasp and immediately apply to obtain research services from others or do research yourself. Johnson makes clear that to succeed in any public agency management position, you have to be able to think analytically and know how to assess the quality of research results. By providing the underlying concepts and just enough methodology to operationalize them, she gives you exactly what you need--in a clear, straightforward way that takes the fear out of learning. You will find here an especially wide range of practical guidelines and examples, all from the author's own and others' experiences in a variety of settings within the public sector.; Throughout her book she emphasizes the "how" of research--how to do it, how to make sense of its findings--and covers all the basic statistical tools, concetrating steadily on interpreting research results. An important, reader-friendly text for students of public administration, and for their often perplexed colleagues already on the job. Johnson explains that public administrators do not do research themselves all that often. But with the rising demand for results measurement, balancing scorecards, benchmarking and assessing customer satisfaction, they do need to understand the basics of what research is and at least have more than just a glimmer of how it is done. Her book offers both--a simple, easily grasped presentation of research concepts and principles, plus all of the essentials of doing program evaluation, policy analysis, and applied social science. It is especially useful as a text in such courses as research methods, program evaluation and introduction to applied statistics, usually found in public administration programs at the undergraduate and graduate levels.; And for people already in jobs outside the academic community, people who are now asked to do tasks that they seldom did before--and never expected they would be asked to do--it is essential
Keywords: Public administration -- Research -- Methodology.; Administration publique (Science) -- Recherche -- Méthodologie.; POLITICAL SCIENCE -- Public Affairs & Administration.; POLITICAL SCIENCE -- Government -- Executive Branch.; Public administration -- Research -- Methodology